Beyond corporate expatriation : examining neglected non-corporate communities - McNulty, Yvonne; Vance, Charles M.; Fisher, Kelly (International Journal of Quality & Reliability Management., 2017)
With this special issue, we sought to broaden our collective understanding of expatriation beyond corporate global mobility. The number of submissions for the special issue reflects a growing interest in non-corporate expatriation from within the management disciplines of IHRM, careers, IM, and IB, as well as across disciplines in the fields mentioned above. The articles cover a variety of sectors from education and religious expatriates to non-profit workers and sports expatriation. Similarly, the sample of the studies covers a broad range of different people and groups from a variety of world regions.